234k views
0 votes
Solve by substitution: y = 3x + 4 and y = -2x – 1.

User Syed Priom
by
4.5k points

1 Answer

3 votes

we have two equation and two variables:


\begin{gathered} y=3x+4 \\ y=-2x-1 \end{gathered}

Now we can substitude the first equation into the second equation:


3x+4=-2x-1

Now we move all the terms with an x to the left and the constants to the right


3x+2x=-1-4

and we simplify


\begin{gathered} 5x=-5 \\ x=-(5)/(5) \\ x=-1 \end{gathered}

Now with the value of x, we can substitude into any equation, I am going to use the first one:


\begin{gathered} y=3x+4 \\ y=3(-1)+4 \\ y=-3+4 \\ y=1 \end{gathered}

User Slevin
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.